Corynebacterium neomassiliense sp. nov., a new bacterium isolated in a stool sample from a healthy male pygmy. (March 2020) - Boxberger, M.; Hasni, I.; Bilen, M.; La Scola, B.
Abstract: An obligate aerobic, Gram-positive, non-sporulating, rod-shaped bacterium designated Marseille P3888 T was isolated from the stool sample of a healthy male pygmy. We described its main characteristics, and sequenced and annotated its genome. The 16S rRNA analysis revealed 98.10% sequence similarity with Corynebacterium terpenotabidum, the phylogenetically closest species with standing in nomenclature. The genome had a size of 3142051 bp with a guanine + cytosine content of 66.83%. We proposed the creation of the new Corynebacterium neomassiliense sp. nov. strain Marseille-P3888 T .